THE RIGHT PLACE OF CAD-COURSES IN ENGINEERING EDUCATION - Szilvási-Nagy, Márta (Periodica Polytechnica Mechanical Engineering, 1992)
An educational conception of teaching CAD for beginners is presented based upon the geometric backgrounds of CAD. Teaching of geometric modelling is proposed as an extension of the fundamental geometry courses.